Differential Fuzzing Go Compilers using LLMs: A Methodological Proposal - Terres, Luiz Paulo Grafetti; Feitosa, Samuel da Silva (Anais da Escola Regional de Engenharia de Software (ERES); 2025: Anais da IX Escola Regional de Engenharia de SoftwareDO - 10.5753/eres.2025.16857, 2025)
Compilers are essential tools for software development. Ensuring their reliability is vital for the security of the software ecosystem. Traditional compiler testing exposes them to many generated programs, but conventional code generators struggle with its own complex implementation and effective test case generation. Recent advancements in Large Language Models (LLMs) and their code-related proficiency present an opportunity to address these challenges. This work proposes a methodology for the differential fuzzing of Go compilers that leverages LLMs as test case generators. The proposed method employs a cross-compiler differential testing strategy to test three compilers: GOLLVM, GCCGO, and the official Go compiler.